International Scientific Conference Youth in the Perspective of the Olympic Movement, Brasov, March 2019 (Transylvania University of Brasov, Faculty of Physical Education and Mountain Sports, 2019)
Kongressband der Internationalen wissenschaftlichen Konferenz "Youth in the Perspective of the Olympic Movement", die im März 2019 im rumänischen Brasov stattfand und von der Transylvania University of Brasov, Faculty of Physical Education and Mountain Sports ausgerichtet wurde.